Development of sound absorption coefficient prediction technique of ultrafine fiber - Yoshio KUROSAWA (Nihon Kikai Gakkai ronbunshu, 2016)
This report deals with sound absorption coefficient prediction technique of ultrafine fiber. As the sound absorption material used for the interior noise reduction of the automobile, the fiber with a diameter of several μm is considered. When a fiber diameter becomes small, usually a sound absorption coefficient increases. But predictive precision was bad by the conventional performance prediction technique. I developed the technique to predict a sound absorption coefficient from the fiber diameter and the fiber density and the material thickness and the material density. The experiment expression of relations was drawn from the experimental results about the flow resistivity and the thermal characteristic length. And I introduce the technique used Limp frame model to predict a sound absorption coefficient for the ultrafine fiber. There diameters are 1-4μm. This paper shows comparison of the experimental results and the calculation results, and this technique is useful.